Muscle oxygen consumption and microvascular function in healthy aging assessed by near-infrared spectroscopy: effect of adipose tissue thickness and physical fitness - van Beekvelt, Mireille; Wilson, Marte; Parviz Gaarden, Andreas (Frontiers in Physiology, 2025)
A decline in skeletal muscle function is a key factor contributing to reduced functional capacity and quality of life with aging. While the mechanisms are multifactorial, impairments in mitochondrial and microvascular function are believed to play a central role. Near-infrared spectroscopy (NIRS) has emerged as a promising non-invasive tool for identifying aging biomarkers and evaluating interventions to preserve muscle health. However, aging often coincides with reduced physical fitness due to lifestyle changes, while age-related changes in body composition further complicate the identification of biomarkers using NIRS. This study investigated aging effects on microvascular and mitochondrial function in healthy adults and explored how physical performance and body composition influence these functions. Eighteen healthy young adults (25.8 ± 2.3 years) and eighteen healthy older adults (69.8 ± 6.0 years) participated. Mitochondrial and microvascular function in arm and leg muscles were simultaneously measured using NIRS during and following vascular occlusion. Physical fitness was evaluated through graded cycling and handgrip tests, and body composition by skinfold thickness and bioimpedance analysis. Data were analyzed using repeated measures ANOVA and multiple regression analysis. Although baseline muscle oxygen saturation (SmO2) was significantly lower in older adults (FDS: 62.8% ± 1.5% vs. 66.6% ± 1.5%; VL: 73.9% ± 2.9% vs. 79.5% ± 2.2%; both P < 0.001), no significant group differences were found in muscle oxygen consumption (mVO2), reperfusion rate (RR), or desaturation/resaturation responses. A significant interaction between muscle and age suggested muscle-specific age-related differences. Multiple regression analysis using forward selection revealed age as a moderate predictor of forearm mVO2, explaining 20.3% of the variance, while adipose tissue thickness (ATT) was the strongest predictor of leg mVO2, explaining 53.9% of the variance. Although the regression analyses should be considered exploratory and interpreted with caution, given the limited sample size and use of forward selection, these findings highlight the complexity of investigating aging effects on muscle function and underscore the importance of accounting for individual fitness and body composition, particularly local ATT, when interpreting NIRS data. To accurately assess age-related differences, future studies should report detailed information on both factors. Addressing these confounders is essential for understanding the physiological impact of aging on muscle function measured by NIRS.